TOOL DEVELOPMENT FOR EVALUATING ADHERENCE TO THE MANAGEMENT IN PATIENTS WITH TYPE 1 DIABETES MELLITUS (T1DM) - Jawad, Mohammad; Afaq, Saima; Ul Haq, Zia; Hussain, Sana; Sarfaraz, Fatima; Hussain, Arshad; Ali, Moosa (Journal of Ayub Medical College Abbottabad, 2025)
Background: Type 1 Diabetes Mellitus (T1DM) is a chronic disease that needs strict adherence to maintain the glycaemic control and prevent complications. However, there is currently a lack of tools specifically designed for low- and middle-income country (LMIC) contexts to monitor adherence to T1DM management. The purpose of this study is to construct a self-administered tool to assess adherence to management protocols in T1DM patients. Methods: The adherence tool was developed in three phases: item pool construction, content validation, and pilot testing. The item pool construction phase consisted of a scoping review, focus group discussions (FGDs) and in-depth interviews (IDIs). In the second phase, expert validation and cognitive interviews were carried out to refine the questionnaire. Then, a pilot study on 25 T1DM patients was conducted to evaluate the tool’s internal consistency and reliability. Thematic and statistical analysis was employed to analyse qualitative and quantitative findings, respectively. Results: The developed tool consists of 43 questions, which covers different aspects of diabetes care including insulin dosage and administration 16 items), diet (12 items), and exercise (15 items). The tool was contextualised to cater for the needs of local patients and is delivered in the local language i.e. Urdu. The pilot study demonstrated good reliability (Cronbach alpha=0.78), test-retest reliability (Cronbach alpha=0.67) showing high internal consistency, and construct validity (Cronbach alpha=0.67) for the developed adherence assessment tool. Also, a strong correlation was found between adherence to overall T1DM management and HbA1C levels. Conclusion: The developed self-administered tool reliably assesses adherence to T1DM management in LMIC contexts. This tool offers a practical resource to monitor and improve glycaemic control in T1DM patients, tailored to local needs.